ANALYSIS OF BANK INVESTMENT ACTIVITIES IN THE SECURITIES MARKET - Yermekova, Zhanna; Saparkul , Ayaulym (Farabi Journal of Social Sciences, 2025)
Purpose. The article examines the investment activities of second‑tier banks in the Republic of Kazakhstan’s securities market during 2022–2024, with a special focus on the strategy and operations of JSC “Bank CenterCredit” (BCC). It aims to analyze the dynamics of BCC’s securities portfolio, its structure, and its role in the bank’s overall profitability. Design/methodology/approach. The study analyzes changes in BCC’s securities investments across 2022–2023 in the context of macroeconomic developments and strategic shifts in asset allocation. It also considers broader sector-wide trends in the banking system’s use of government bonds and National Bank notes. Findings. In 2022, BCC significantly increased its investments in government and other debt securities amid high interest rates and the acquisition of another bank’s assets. In 2023, the bank partially redirected liquidity into lending, reducing the share of its securities investments. Kazakhstani banks overall rely heavily on securities as key sources of income and liquidity, but their high yields have drawn regulatory attention. Originality. The article offers practical recommendations for balancing lending and investment strategies in commercial banks, managing interest-rate risks, and enhancing the development of Kazakhstan’s securities market. The findings are relevant for both commercial banks and financial market regulators. Key words: bank investments, securities, bonds, stock market, liquidity, Bank CenterCredit, Kazakhstan.